Evolutionary approaches to understanding crime: explaining the gender gap in offending - Durrant, Russil (Psychology, crime & law, 2019)
Evolutionary approaches have the potential to make significant contributions to our understanding of criminal offending. In particular, an evolutionary perspective can help in the development of more comprehensive explanations for the main correlates of offending such as gender, age, and social class. In this article I argue that that an evolutionary perspective that draws on the conceptual resources of the extended evolutionary synthesis can help us to explain why men are more likely to be perpetrators of crime compared to women. First, I will outline the key conceptual characteristics of the extended evolutionary synthesis and tease out the implications of this approach for understanding the evolution of human behaviour. Next, I will discuss how an evolutionary approach can help us to understand the gender gap in offending. I will then present a model which outlines how an extended evolutionary perspective can usefully integrate different kinds of explanation to provide a more comprehensive explanatory account of gender differences in crime. I conclude by considering some of the wider implications of this model for crime prevention.